Odpowiedzi

2009-11-04T19:19:19+01:00
Pisze bez przykładów
samo rozwiązanie

a) (½x²y)² +2*½x²y*2xy² + (2xy²)² = ¼x⁴y² + 2x³y³ + 4x²y⁴

b)(2x²)²-2*2x²*3/2x + (3/2x)² = 4x⁴ - 6x³ + 3/2x²

c)(½ab)² - 2*½*4c² + (4c²)² = ¼a²b² - 4abc² + 16c⁴

d) (4ab)² - 2*4ab*½ - ½² - (½²-2*½*6ab + (6ab)²)² = 16a²b² - 4ab + ¼ - (¼ - 6ab + 36a²b²)= 16a²b² - 4ab +¼ - ¼ +6ab - 36a²b²=-20a²b² + 2ab

e) 2(5x² + 2*5x*3 + 3²)-3(4²-2*4*7x + 7x²) = 2(25x² + 30x + 9)-3(16 - 56x + 49x²) = 50x² + 60x + 18 -48 + 168x - 147x² = -97² + 228x - 30


gotowe